Implementasi Program Pemberian Makanan Tambahan Pemulihan (PMT-P) pada Balita untuk Menurunkan Prevalensi Stunting di Puskesmas Kabupaten Jember - Rahmawati, Irnia Zain; Herawati, Yennike Tri; Utami, Sri (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
Jember Regency is included in the five cities/regencies with the highest prevalence of stunting in East Java, with a percentage ranging from 40-45%. One of the interventions for toddlers to reduce the prevalence of stunting is the Recovery Supplemental Feeding (PMT-P). The study aimed to study the implementation of the Recovery Supplemental Feeding (PMT-P) program for toddlers to reduce the prevalence of stunting. This is a qualitative approach. The data was collected by in-depth interviews and documentation. The results showed that the implementation of the PMT-P Program was not fully in accordance with the 2011 PMT-P Guidelines from the Indonesian Ministry of Health, the program implementers had good insight, knowledge, and response in implementing the PMT-P program. The output of the PMT-P program implementation was not in accordance with David C. Korten's theory of suitability. It is suggested to cook together among midwives, cadres, and mothers of target toddlers, create a community of toddlers’ mothers as a sharing platform about the implementation of Recovery Supplemental Food, and increase monitoring in the provision program for toddlers to ensure that supplemental food is actually consumed by the target toddlers.